BECOMING AUTHENTIC TEACHERS THROUGH TRANSFORMATIVE INQUIRY: FINAL PRACTICUM CHALLENGES - Tse, Vanessa V.; Abra, Meaghan; Tanaka, Michele T. D. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
Within the final teaching practica, pre-service teachers encounter the crucial challenge of redefining their teacher identities. Leaving behind personas formed as students, professional settings necessitate asking themselves what kind of teacher they want to be in a new context. In collaboration with their professor, two pre-service teachers examined their final practicum experiences, highlighting how Transformative Inquiry (TI), a holistic investigative approach, supported them in becoming authentic teachers. We hear how the TI process helped them identify, honour, and strengthen their personal and unique teaching identities. Highlighted themes include: touchstone stories, the power of the circle, living the questions, and the importance of on-going reflection. These new teachers resisted traditional images of teachers by embracing imperfection and vulnerability. DEVENIR D’AUTHENTIQUES ENSEIGNANTS PAR LE BIAIS DE LA RECHERCHE TRANSFORMATIVE : LES DÉFIS DU DERNIER STAGE Au cours du dernier stage en enseignement, les futurs enseignants font face à un défi important: redéfinir leur identité comme enseignant. En effet, oeuvrant dans un nouveau milieu — en contexte professionnel — ils doivent abandonner leur identité étudiante et se questionner sur le type d’enseignant qu’ils désirent être. En collaboration avec leur professeur, deux futurs enseignants ont analysé les expériences vécues durant leur dernier stage, mettant en lumière la manière dont l’approche de Recherche Transformative (RT ou Transformative Inquiry), une méthode de recherche holistique, les a aidés à devenir de véritables enseignants. Dans cet article, nous apprenons comment la RT leur a permis de développer, d’accepter et de renforcer leur identité pédagogique personnelle et unique. Les auteurs abordent des histoires marquantes, le pouvoir du cercle, le concept d’incarner le questionnement et l’importance de la réflexion constante. Les futurs maîtres se sont opposés à la conception traditionnelle de l’enseignant et ont accepté d’être imparfaits, ainsi que vulnérables.